Suspended soils enrich local forest floor soils during the rainy season in a tropical monsoon rainforest of Hainan Island, South China - Xu, Shitao; Wang, Yachen; Yu, Xudong; Cai, Zeping; Ren, Mingxun (Frontiers in Plant Science, 2024)
Epiphytic plants are abundant in rainforests and often serve as traps for litter and dust falling from the canopy. As it accumulates, this material can form nutrient-rich soils, which are likely involved in local nutrient cycling and ecological processes. To explore spatial and temporal variation in the influence of suspended soils on local nutrient cycles, we compared the physical, chemical and biological properties of suspended soils from the locally-dominant epiphytic bird's nest fern (Asplenium nidus L.) to those of three types of forest floor soils (soil collected from upslope, downslope, and underneath the host tree) in a tropical monsoon rainforest in Bawangling National Nature Reserve on Hainan Island, China. Suspended and forest floor soils were all acidic, with suspended soils having much higher organic matter (66.84%) and water content (~300%) than forest floor soils. Suspended soils contained significantly more available nitrogen, phosphorous, and potassium and had much higher urease, cellulase, and catalase activities, indicating that they harbored diverse microbial communities with higher decomposition and biomineralization activity. Physicochemical traits of suspended soil and soil collected from under the host tree were significantly more similar in the rainy season than in the dry season, suggesting that suspended soils may contribute to local nutrient cycling as they are flushed out of epiphytic plants and enrich stemflow and forest floor soils. Thus, suspended soils play a role in local nutrient cycling, especially during the rainy season. This study provides empirical support for the seasonality and heterogeneity of forest floor soil enrichment by suspended soils in tropical monsoon rainforests.